(untitled) (Research, Society and Development, 2024)
Objective: To analyze the level of physical activity of people with hypertension and diabetes during the Covid-19 pandemic. Materials and Methods: This is an exploratory, descriptive, cross-sectional study with a quantitative approach. Data collection took place through the sharing of three electronic questionnaires (Sociodemographic, International Physical Activity Questionnaire-IPAQ and on the practice of physical activity during the Covid-19 pandemic), adapted for Google Forms, and sent through a link to social networks, between the period of November and December/2020. The sample consisted of 77 individuals with hypertension and diabetes, with an average age of 54.1±12.7 years. Most of the sample surveyed showed different levels of physical activity during the pandemic, such as very active; active and irregularly active. The most practiced physical activities were walking, gymnastics, weight training and cycling. Regarding the difficulties of practice, low motivation, inappropriate physical space, self-organization of time and lack of professional guidance were identified. It was also identified that the most perceived physical and emotional aspects were symptoms of anxiety, stress, musculoskeletal pain and increased body fat. In view of the above, it was noticeable that social isolation directly and/or indirectly affected health and the maintenance of a physically active routine during the pandemic context, consequently due to the restrictions aimed at closing spaces for physical activity.